Hydrophobization of Chitin Nanofibers by Grafting of Partially 2-Deoxygenated Amyloses Through Enzymatic Approach - Naoki Yamamoto; Masayasu Totani; Jun-ichi Kadokawa (Molecules)
In recent years, increased attention has been given to the effective use of chitin nanofibers (ChNFs). We have developed a method to fabricate thinner chitin nanomaterials, called scale-down chitin nanofibers (SD-ChNFs), by a bottom-up procedure at the nanoscale level, with subsequent disintegration by electrostatic repulsion. The surface modification of SD-ChNFs is anticipated to provide new properties and functions for their practical applications. Inspired by our previous reports, which found hydrophobicity in partially 2-deoxygenated (P2D-) amylose obtained by the glucan phosphorylase (GP)-catalyzed enzymatic copolymerization of α-d-glucose 1-phosphate/d-glucal as comonomers, this work investigated the hydrophobization of SD-ChNFs via an enzymatic approach. After the modification of maltooligosaccharide primers on SD-ChNFs was performed by a reductive alkylation toward ChNFs, the grafting of the P2D-amyloses was performed by GP-catalyzed enzymatic copolymerization. 1H NMR analysis supported the production of P2D-amylose-grafted SD-ChNFs with different d-glucose/2-deoxy-d-glucose unit ratios on SD-ChNFs. The X-ray diffraction analysis of the products confirmed that the chain lengths and unit ratios of the grafted polysaccharides strongly affected the entire crystalline structures. Water contact angle measurements of the cast films of the products indicated that successful hydrophobization was achieved by the grafting of P2D-amylose chains with a sufficient chain length, a relatively high 2-deoxy-d-glucose unit ratio, and low crystallinity.